2005
DOI: 10.1186/1476-4598-4-22
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation and histone deacetylase activity of magnesium valproate in tumor and peripheral blood of patients with cervical cancer. A phase I study

Abstract: Background: The development of cancer has been associated with epigenetic alterations such as aberrant histone deacetylase (HDAC) activity. It was recently reported that valproic acid is an effective inhibitor of histone deacetylases and as such induces tumor cell differentiation, apoptosis, or growth arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(38 citation statements)
references
References 43 publications
0
37
0
1
Order By: Relevance
“…Several other groups (Imai et al 2003;Roh et al 2004;Watanabe et al 2005) have reported growth inhibition and sensitization to Fas-mediated cell death of human osteosarcoma cells by HDAC inhibitors, FR901228 and TSA, but not inhibition of soluble Fas secretion. Importantly, our results showed that VPA exerted its eVects at concentrations which are attainable in sera of patients administered with VPA orally without serious side eVects (Johannessen and Johannessen 2003;Chavez-Blanco et al 2005;Allen et al 2006;Ueshima et al 2008). These results indicate the possibility that VPA may be applicable to the treatment of osteosarcomas.…”
Section: Discussionmentioning
confidence: 57%
“…Several other groups (Imai et al 2003;Roh et al 2004;Watanabe et al 2005) have reported growth inhibition and sensitization to Fas-mediated cell death of human osteosarcoma cells by HDAC inhibitors, FR901228 and TSA, but not inhibition of soluble Fas secretion. Importantly, our results showed that VPA exerted its eVects at concentrations which are attainable in sera of patients administered with VPA orally without serious side eVects (Johannessen and Johannessen 2003;Chavez-Blanco et al 2005;Allen et al 2006;Ueshima et al 2008). These results indicate the possibility that VPA may be applicable to the treatment of osteosarcomas.…”
Section: Discussionmentioning
confidence: 57%
“…Plasma levels progressively decreased until the end of treatment. However, the mean value in the lowest (four-cycle) determination was >75 µg/mL, which is an effective concentration [28].…”
Section: Discussionmentioning
confidence: 82%
“…Assays were performed using the colorimetric HDAC activity assay from BioVision (BioVision Research Products, Mountain View, CA, USA) according to manufacturer instructions, as described [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although active in reinducing H3 and H4 acetylation in tumour cells, the clinical efficacy seems limited [103].…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%